The Impact Of Product Quality And Post-Purchase Service Quality On Customer Satisfaction Of Hp Vivo In Semarang City - Izzatul Millah; Aulia Nabila Salsabila Addintami; Adhe Novita Indrayani; Riyan Febriyanto; Ratih Pratiwi (CV Putra Publisher, 2022)
This study aims to describe and analyze the impact of product quality and post-purchase service quality on HP VIVO customer satisfaction in Semarang City. This study uses quantitative methods. The sample in this study was 96 respondents who were taken by using accedintal sampling technique (by chance). Data collection was carried out through the distribution of questionnaires with a Likert measurement scale of 1 to 5 and the data obtained were then analyzed using the SPSS statistical analysis tool. The results showed that the product quality (X1) had a positive beta value of 0.132 with a level of sig.0.125> 0.05. This means that the product quality variable has a positive but not significant effect on HP VIVO customer satisfaction in Semarang City. The service quality variable (X2) has a positive beta value of 0.679 with a level of sig.0.000 <0.05. That is, the service quality variable has a positive and significant influence on HP VIVO customer satisfaction in the city of Semarang.